Could an economy get stuck in a rational pessimism bubble? The case of Japan - Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2023)
Developed economies have experienced slower growth since the 2008 Önancial crisis, creating fears of "secular stagnation." Rational expectations models have forward-looking bubble solutions, which could cause this; here we investigate the case of Japan. We show that a New Keynesian model with a weak equilibrium growth path driven by pessimism sunspot belief shocks matches economic behaviour. Another possibility is a conventional model where productivity growth has simply slowed down for unknown reasons. Nevertheless, a welfare-optimising approach implies Öscal policy should commit to eliminating the potential sunspot while being prepared to revert to normal policy if ináation rises.
Keywords: E5; E6; E32; 330; Secular stagnation; Pessimism sunspot; Indirect Inference; DSGE model